Boron Coordination Effect in Ni−Nx Doped Graphene Catalysts on the ORR Performance Based on DFT Calculations. Issue 1 (10th November 2021) - Zhang, Jingyu; Cao, Da; Liu, Hui; Wang, Fangqing; Liang, Limin; Liu, Caichi; Hao, Qiuyan; Li, Ying
Abstract: The coordination atoms of metal active site in transition metal N‐doped carbon single atom electrocatalysts play a vital role in dominating the catalytic performance of oxygen reduction reaction (ORR) at the cathode of fuel cells or metal‐air cells. In view of weak adsorption ability of Ni active site in NiN4 −C catalysts to oxygen intermediate states, herein we introduce boron atoms with smaller electronegativity than N and C atoms to modulate the local coordination environment and electronic structures of Ni site. First‐principles density functional calculations reveal that both B substitution for N atoms (NiN2 B2 −C) and B coordinating with N and C (NiN4 B8 −C) can effectively optimize the Gibbs free energy of oxygen intermediate states and hence improve the catalytic activity of the materials. In addition, we propose that the trend change in catalytic activity is mainly governed by the filling of antibonding orbitals between Ni‐3d and O‐2p states near the Fermi level. Abstract : Single‐atom catalyst is designed via graphene‐supported NiNx . Different number of boron atoms are doped into different positions of NiNx to improve the ORR activity. NiN2 B2 −C and NiN4 B8 −C exhibit remarkable ORR performance with computed overpotentials of 0.58 and 0.62 V, respectively.